Implementation of Straight Liability and Liability Based on Fault Concepts in Environmentally Sound Economic Development in Indonesia - Siagian, Fahrizal S.; Saragih, Geofani Milthree; Firouzfar, Saied (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to answer problems related to the regulation of the concept of punishment in environmental aspects in the Indonesian criminal justice system. Secondly, this research aims to answer the juridical implementation of the concept of Straight Liability and Liability Based On Fault in environmentally sound economic development in Indonesia. This research uses normative legal research that focuses on primary, secondary, and tertiary legal materials. This research obtained several important points including legal arrangements related to the concept of environmental crime regulated in Law Number 32 of 2009 concerning Protection and Management of the Indonesian Environment. Second, the implementation of the concept of Straight Liability and Liability Based On Fault in environmentally sound economic development in Indonesia so far has not been maximised. This is due to the lack of mentality and consistency of law enforcement officials to enforce environmental law in a complex manner. So that this research proposes to strengthen the essence and existence of law enforcement officials in enforcing environmental law in order to preserve Indonesia's environmental ecosystem.